Efektivitas Lesson Study Pada Mata Pelajaran Ekonomi untuk Meningkatkan Motivasi dan Prestasi Belajar di SMA Mutmainah - Amrin, Sayful (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to find out: (1) the effectiveness of lesson study in increasing the economics learning motivation of class XII students at Mutmainah High School; (2) the effectiveness of lesson study in improving the economics learning achievement of class XII Mutmainah High School students; (3) differences in motivation to learn economics using lesson study and those not using lesson study among class XII students at Mutmainah High School; (4) differences in economic learning achievement that use lesson study and those that do not use lesson study in class XII Mutmainah High School students. This research is quasi-experimental research with a research design of one factor, two samples and one covariable. The population of this study were class XII students at Mutmainah High School. The sample for this research was students in class XII A (control class) and XII B (experimental class). The techniques used to analyze data are normality test, homogeneity test, hypothesis test (test). The results of the research on the first hypothesis test show that lesson study is effective in increasing learning motivation with an average increase value of 13.22% and a significance level (I-tailed) of 0.001 or <0.05 which shows that students' final learning motivation is better than learning motivation. beginning in the experimental class. The second hypothesis shows that lesson study is effective in increasing student learning achievement with an average increase of 83.95% with a significant level (I-tailed) of 0.001 or <0.05 and a tcount of -17.681 which shows the post-test score is better than post-test scores in the experimental class. test the third hypothesis